Saisir les dynamiques de minorisation sociale dans les espaces publics verts des quartiers populaires urbains en France, depuis le point de vue du jardinier municipal - Elsa Koerner (Genre, Sexualité et Société)
The study of gender relations in the practices of public space, from the standpoint of the public gardeners, shows the complexity of the intertwined relations of power and social hierarchies. With the theoretical framework of the social minorisation built by Colette Guillaumin, this paper addresses how public servants view the working-class districts as places where gender inequalities are tangible. Cross-cutting issues of cultural alterisation, spatial and institutional hierarchies, property and production contribute to the perpetuation of gender categories, with the risk of aiming for the feminisation of public space, at the expanse of men pertaining to social minorities. Moral discourse is central to the way municipal gardeners describe the uses of public gardens. It is through this discourse that we can understand the relationships of cohabitation between different fractions of the working classes in those public spaces.